Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) antibody prevalence in a healthcare worker population exceeded self-reported infection rates, 2020 - Susan E. Hoover; Valerie Reed (Cambridge University Press, 2022)
A study of severe acute respiratory coronavirus virus 2 (SARS-CoV-2) seroprevalence at a healthcare institution prior to the availability of vaccine showed that seroprevalence in the cohort increased over 6 months from 25% to 55%. The number of employees with antibodies was higher than the number who reported an exposure or diagnosis at each time point.